PROTECTION OF DOMESTIC INDUSTRY RESULT OF ACTION DUMPING ACTIONS ACCORDING TO GATT-WTO PROVISIONS IN THE ASEAN ECONOMIC COMMUNITY - Mhd Nasir Sitompul (Proceeding International Seminar of Islamic Studies, 2022)
The aim is to protect national business. The purpose of this study is to examine and analyze the protection of domestic industries due to dumping in the Asean Economic Community according to the GATT-WTO provisions in Indonesia.This research is a type of normative research, where the main sources of legal materials are primary legal materials and secondary legal materials by collecting legal materials, both laws and regulations, scientific works of scholars as well as legal concepts, theories, opinions. legal opinions or findings. The legal materials are clarified according to their respective studies in accordance with the subject matter so that they can produce an answer to each problem.Presence of the MEA, Indonesia has the opportunity to take advantage of the advantages of domestic economies of scale as a basis for making profits. For this achievement. the government must formulate and determine integrated strategic steps by involving all components of the nation and stakeholders. The government must also intensify the socialization activities of the Asean Economic Community to the entire community, including the ranks of the bureaucracy in the regions aim of avoiding overlapping between national policies and regional policies that always base decision making based on regional autonomy.Keywords: Protection, Domestic Industry, MEA, GATT-WTO